1998
DOI: 10.1135/cccc19981575
|View full text |Cite
|
Sign up to set email alerts
|

Towards Synthesis of Calysterols, Marine Sterols with Cyclopropene Moiety in the Side Chain: Synthesis of 26,27-Dinor-23H-isocalysterol

Abstract: 26,27-Dinor-23H-isocalysterol 24 has been synthesized in 19% yield (6 steps) from ethyl 6β-methoxy-3α,5-cyclo-5α-pregnan-21-oate (18). For construction of the side chain, alkylation of lithium salt of ester 18 with 1-bromo-1,2-dimethyl-c-3-iodomethyl-c-2-(trimethylsilyl)cyclopropane 16 was used. It has been shown that reduction of the ester group in position 21 and rearrangement of the 3,5-cyclosteroid system are compatible with the sidechain functionalities. It has been found that methylation of 1,1-dibromo-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Halogen-metal exchange between gem-dihalocyclopropanes and alkyllithium leads to cyclopropylidene lithium halocarbenoids. These compounds are quite stable at low temperatures (∼-100 °C) and can react with electrophiles such as alkyl halides, 176,184,205,354 trimethylsilyl or stannyl chlorides, carbon dioxide, 355 aldehydes, 356,357 acid chlorides, ketones, 205 and iminium salts to form the appropriate products of substitution at the C1 carbon atom. Some recent examples are given below (eqs 73 205 and 74 355 ).…”
Section: Iv3 Halogen−metal Exchange and Further Reactions Of 1-halo-1...mentioning
confidence: 99%
“…Halogen-metal exchange between gem-dihalocyclopropanes and alkyllithium leads to cyclopropylidene lithium halocarbenoids. These compounds are quite stable at low temperatures (∼-100 °C) and can react with electrophiles such as alkyl halides, 176,184,205,354 trimethylsilyl or stannyl chlorides, carbon dioxide, 355 aldehydes, 356,357 acid chlorides, ketones, 205 and iminium salts to form the appropriate products of substitution at the C1 carbon atom. Some recent examples are given below (eqs 73 205 and 74 355 ).…”
Section: Iv3 Halogen−metal Exchange and Further Reactions Of 1-halo-1...mentioning
confidence: 99%
“…191 The synthesis of marine sterols with polyhydroxylated side chains has continued to attract interest. [192][193][194][195] Attention has also been directed at the cytotoxic 9,11-secosterols 95 isolated from the soft coral, Gersemia fruticosa. [196][197][198] Considerable attention has been paid to the brassinosteroid plant growth promoting substances.…”
Section: Cholic Acidsmentioning
confidence: 99%
“…Some model experiments verified important points of this plan and also indicated that an i-steroid system (6β-methoxy-3α,5-cyclo-) could be used for temporary protection of the latent C-3 hydroxy group and the C-5,C-6 double bond in isocalysterol. [20] In a first series of experiments, we set out to synthesize a dibromo-trimethylsilyl intermediate corresponding to iii, where Y ϭ SiMe 3 and X ϭ Br (Scheme 1). Its methyl-cholestane carbon skeleton, which was transformed into the corresponding C-21 methyl derivative 13 in the standard manner via alcohol 12a and tosylate 12b.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, 4-methyl-1-trimethylsilylcyclohex-1-ene has been found to react readily with dichlorocarbene [39] and our own model experiments concerning the addition of dibromocarbene to some vinylsilanes were encouraging. [20] The lack of reactivity of compound 13 suggests that the combined steric effect of the trimethylsilyl and isopropyl groups prevents the reagent from gaining access to the double bond.…”
Section: Introductionmentioning
confidence: 99%